The Influence of Emotional Well-Being and Spiritual Wholeness on Midlife Positive Functioning of Middle-Aged Professionals - Chris Feli Joy P. Tajonera; Rigel Kate Y. Lamig (Philippine Social Science Journal, 2021)
This descriptive-correlational study focused on the emotional well-being, spiritual wholeness, and positive functioning of middle-aged professionals. It aimed to measure the levels of emotional well-being, spiritual wholeness, and positive functioning; likewise, their difference when age, sex, civil and employment status, and job rank were considered.  This research also intended to determine the relationship among the mentioned constructs. The study utilized tests on Emotional Well-being, Spiritual Wholeness, and Psychological Well-being Scale.  Eighty-three participants from the university in Bacolod City were purposively chosen to answer these tests. Findings revealed that the levels of emotional well-being and spiritual wholeness of midlife adults were very high. Also, no significant differences in both constructs were found.  The positive functioning of the respondents is high.  However, an average positive functioning of single respondents was revealed when the civil status was considered. It was concluded that both emotional well-being and spiritual wholeness are significantly related to the positive functioning of midlife adults. The results of the study will be utilized for the creation of a wellness program, which aims to improve the employee’s psychological well-being.